ENERGY AND QOS AWARE LINK QUALITY BASED CLUSTERING PROTOCOL (EQ-LQBC) IN WIRELESS BODY AREA NETWORKS (Journal of Pharmaceutical Negative Results, 2023)
Wireless Body Area Networks are networks of sensor nodes embedded in and around the human body that collect bio-signals for a range of applications including patient monitoring, gaming, and so on. Many developers around the world are researching the WBAN network concept. WBAN has had a technological boom in the previous decade as a result of developments in MEMS and wireless communication technology. In the Wireless Body Area Network, there are a few key elements to keep in mind. Unlike wireless sensor networks, the WBAN monitoring environment is limited to the human body, has a heterogeneous data rate, requires biocompatible sensor devices, and has a more changeable network topology due to body movement. This paper presents a method based on queue length, distance nearest from sink and energy of the node use of the parameters to select the optimum cluster head. EQ-LQBC selects the cluster head dynamical based on time interval. In the next step to achieve the same step repeat on intra cluster network on WBANs. The obtained results show a major improvement of EQ-LQBC in terms of network stability, network life time, throughput, end-to-end delay and packet delivery ratio.